A Study on Lightweight Cryptography Algorithm for IoT based Bicycle Sharing System - Bajracharya, Larsson; Jeong, Jongmun; Hwang, Mintae (International Journal of Engineering and Technology, 2018)
In this paper, we studied lightweight cryptography for IoT based Bicycle Sharing System. We maintained a remotely located real time server and four separate stations with kiosk control box system, designed with Internet based IoT devices. Then, we calculated the processing time to unlock the bicycle from each station, once the request was sent to the server. The calculated load and processing time were compared after the application of   cryptography algorithm. The comparison helped us conclude that the LEA cryptography showed minimal time difference when applied in a real time system. At the same time, highly secure data transmission was also achieved.